Perceived Benefits and Challenges of Using ChatGPT in Designing Lesson Plans: A Case Study at President Elementary School, Bekasi, Indonesia - Mikha M.C. Manurung; Emilius German (Institut of Shanti Bhuana, 2026)
Artificial Intelligence (AI) is transforming education, with generative tools like ChatGPT increasingly supporting teaching practices. One key application is lesson planning, where AI enhances efficiency, creativity, and personalization. However, its use in primary education, particularly in Indonesia, remains underexplored. This study examines elementary school teachers’ perceptions of using AI, specifically ChatGPT, in lesson planning. It investigates the perceived benefits, challenges, and strategies for effective integration. An explanatory sequential mixed methods design was employed, combining quantitative surveys and qualitative interviews to provide a comprehensive understanding of teachers’ experiences. The survey phase captured broad patterns of AI use, which then informed the in-depth interviews conducted after one month of AI implementation. Findings reveal that teachers view AI as a valuable tool that simplifies lesson planning, improves efficiency, and supports the creation of structured, engaging, and personalized learning materials. Despite these benefits, challenges emerged, including inaccuracies and biases in AI-generated content, limited training and digital literacy, and concerns over over-reliance that could reduce creativity and critical thinking. This study concludes that while AI holds significant potential to enhance lesson planning in primary education, its success depends on thoughtful, ethical, and well-supported implementation. It is recommended that schools provide continuous professional development, clear guidelines for ethical AI use, and reliable access to advanced AI tools to empower teachers to integrate AI effectively and responsibly into their lesson design processes.